Transient infantile hypertriglyceridaemia due to homozygous mutation in GPD1 presenting in childhood with hepatic adenoma. Issue 4 (1st April 2022) - Kumar, Karunesh; Malhotra, Smita; Sibal, Anupam
Abstract : Hypertriglyceridaemia in infancy is usually secondary to underlying metabolic disorder which usually has a genetic basis unlike the adult population. One such recently described entity is transient infantile hypertriglyceridaemia (HTGTI). In this disorder, mutation in glycerol-3-phosphate (G3P) dehydrogenase gene leads to deficiency of G3P dehydrogenase resulting in hypertriglyceridaemia and hepatomegaly. Clinical features tend to improve with age but may develop fibrosis. Our patient presented in infancy with hypoglycaemia, hepatomegaly, high transaminases and hypertriglyceridaemia. Limited genetic test for glycogen storage disorder was negative and was kept under follow-up. On follow-up, he developed hepatic lesion and his hepatomegaly with hypertriglyceridaemia persisted. There are only a few cases reported worldwide and none has reported development of adenoma so far. This could be the first report of development of adenoma in transient HTGTI.